Gaming for Growth: Investigasi Manfaat Akademik dan Kognitif dari E-Learning Berbasis Petualangan di Sekolah Menengah - Zakirman, Zakirman; Rahayu, Chichi; Widiasih, Widiasih (STAI Auliaurrasyidin Tembilahan, 2024)
The use of technology in digital learning can enhance students' learning experience and open new opportunities to create innovative and engaging learning methods, especially at the high school level. This study aims to determine the impact of using adventure game-based e-learning on academic and cognitive of SMA N 3 Mandau students in Riau Province. The study used a mixed methods approach with a sample of 30 randomly selected grade X students. Quantitative data were collected through cognitive tests and questionnaires, while qualitative data were obtained through interviews and observations. The research procedure included pre-intervention, game implementation, monitoring, and data analysis. Quantitative data analysis using descriptive statistics and t-test, showed an increase in average learning outcomes from 59.6 to 78 with a correlation of 0.706, indicating a strong positive relationship between the use of the game and improved learning outcomes. Qualitative analysis using thematic analysis, showed a significant increase in academic and cognitive achievement of students who participated in the adventure game-based e-learning program.